The effect of auditor competence and independence on audit quality - Siti Nur Mawar Indah (Indonesia Auditing Research Journal, 2022)
The Public Accountant (auditor) profession is like a "double-edged sword", on the one hand auditors must pay attention to the credibility and ethics of the profession, but on the other hand they must also face pressure from clients in various decision-making. must face pressure from clients in various decision-making auditor's decision making. If the auditor is unable to resist pressure from clients such as personal, emotional or financial pressure, the auditor's independence will be compromised. personal, emotional or financial pressure, the auditor's independence has been reduced and can affect audit quality. and can affect audit quality. This study aims to analyze and prove empirical evidence of the effect of experience, knowledge, length of contact with clients, pressure from clients, peer review, and non-audit services provided by KAP on audit quality. provided by KAP on audit quality. The sample used was 79 respondents, namely auditors at 18 KAPs in Semarang City. Meanwhile, to answer the research hypothesis using multiple regression analysis tools analysis tool, after previously testing classical assumptions. Based on the results of the study, it can be concluded that experience in conducting audits, the knowledge of an auditor and the review of fellow auditors (peer review) have a positive effect on audit quality. So that the more deeper and broader the knowledge of an auditor and the more experienced in the field of auditing as well as peer review from fellow auditors (peer review). auditing field as well as peer review from fellow auditors, the better the audit quality will be. better the quality of the audit performed. Meanwhile, the length of the relationship with the client, pressure from clients, and non-audit services provided by KAP.